Sprawozdanie z III ogólnopolskiej studencko-doktoranckiej konferencji naukowej Państwo – Kościół – Wartości, Wrocław 2016 - Debita, Magdalena (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
Article reports the course of the third national student-doctoral scientific conference State – Church –Values, which was held at the Faculty of Law, Administration and Economics of the University of Wroclawon December 19th 2016. During the conference occurred more than thirty researchers from six researchcenters from all over Poland
Keywords: kościoły; sprawozdania; państwo; wartości; prawo; konferencje